Pengaruh Kepemimpinan, Lingkungan Kerja dan Kompensasi Terhadap Produktivitas Kerja Pegawai Balai Teknik Perkeretaapian Kelas II Wilayah Sumatera Bagian Selatan Dengan Kepuasan Kerja Sebagai Variabel Intervening - Farah Dina Eka Syamriati; H. Sulbahri Madjir; Djatmiko Noviantoro (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine and prove the influence of leadership, work environment and compensation on work productivity of employees of the Class II Railway Engineering Center for Southern Sumatra Region with Job Satisfaction as an Intervening Variable either directly or indirectly. The population in this study were all employees of the Class II Railway Engineering Center for the Southern Sumatra Region, while the sample was part of the population that would be the object of research. In this study, the total population was 91 people. Sampling in this study used the Saturated Sample technique, namely sampling was carried out as a whole from the total population. In line with the opinion above, in this study, by considering a population of 91 people, the authors took a total of 91 people as research samples. The data analysis used in this study was to use the Structural Equation Model (SEM) analysis method which was operated through the Partial Least Square (PLS) program.